Effect of oil pulling on the Streptococcus mutans concentation in plaque around orthodontic brackets -A prospective clinical study - Nithya Jagdish; Sridevi Padmanabhan; Arun B. Chitharanjan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Fixed orthodontic appliances create areas of plaque stagnation leading to an increase in the volume, structure, and composition of plaque. This increases the chances of decalcification and white spot lesions. Oil pulling, an ancient practice involving swishing oil in the mouth, has demonstrated a significant reduction in plaque scores after 45 days, and a reduction in salivary Streptococcus mutans concentration in few studies done in nonorthodontic subjects. The aim was to compare the concentration of S. mutans in plaque around orthodontic brackets in patients using oil pulling with sesame oil and those on routine oral hygiene. Subjects and Methods: Twenty subjects requiring fixed orthodontic treatment were divided into two equal groups: Group A-Oil pulling and Group B-Control. All subjects were instructed to follow common oral hygiene methods and in addition, Group A was instructed to perform oil pulling for 30 days starting 1 month after placement of fixed appliances. Plaque specimens were collected from labial surfaces of maxillary lateral incisors and quantification of S. mutans was done using real-time polymerase chain reaction. Mean and standard deviations for descriptive statistics, paired, and unpaired sample t-tests were analyzed. Results: Comparison of S. mutans concentration between T1 and T2 demonstrated a significant difference in both control and study groups. The experimental group showed significantly lesser S. mutans concentration compared to the control group. Conclusions: Oil-pulling therapy with sesame oil resulted in a statistically significant reduction in the concentration of S. mutans in the plaque around orthodontic brackets.